Ermüdungsbruchversagen hartstoffbeschichteter Werkzeugstähle in der Kaltmassivumformung - Hinsel, Christian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2000)
The application of modern hard coatings provides a considerable potential to increase tool life if wear is the dominating reason for failure. Particularly in cold forging, however, tool life is often limited by fatigue and the resulting crack initiation. The Dr.-Thesis discusses the issue in which way different hard coatings influence the fatigue behaviour of tools steels. The results of fundamental low- and high-cycle fatigue experiments lead to conclusions which properties (especially residual stresses and surface topography) of the coated steel influence its strength in which way. Therefore a cold working steel (X 155 CrVMo 12 1) and a high-speed steel (S 6-5-2), coated with various materials by PVD and CVD, were investigated. Inferences from the experimental and numerical analysis of the residual stress distribution in coating and substrate provide insight into the load conditions. Thus, the decisive factors which influence the fatigue behaviour of coated tool steels are determined. Furthermore, the capabilities of surface and coating technologies to reduce the risk of premature fatigue crack initiation are discussed. The results of tool monitoring of cold forging punches demonstrates how advanced duplex treatment (plasma-nitriding and subsequent PVD coating) succeeds in increasing the tool life considerabl